2019
DOI: 10.1017/s0144686x19000795
|View full text |Cite
|
Sign up to set email alerts
|

Does having highly educated adult children reduce mortality risks for parents with low educational attainment in Europe?

Abstract: It is known that the education of significant others may affect an individual's mortality. This paper extends an emerging body of research by investigating the effect of having highly educated adult children on the longevity of older parents in Europe, especially parents with low educational attainment. Using a sample of 15,015 individuals (6,620 fathers and 8,395 mothers) aged 50 and above, with 1,847 recorded deaths, over a mean follow-up period of 10.9 years from the Survey of Health, Ageing and Retirement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
2
8
0
Order By: Relevance
“…On the other hand, the advantages of children's education for parental old-age health may 'cumulate' over a parent's life course, leading to larger differences in health by children's education as parents age (Ross and Wu 1996;Dannefer 2003). While a considerable amount of evidence suggests that age may be a leveller in high-income settings (Friedman and Mare 2014;Zimmer et al 2016;Elo et al 2018;Wolfe et al 2018;Sabater et al 2019;Yahirun et al 2020), relatively little is known about the age gradient in low-resource settings. Similarly, the benefits of children's education may also vary by geographical region.…”
Section: Effect Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the advantages of children's education for parental old-age health may 'cumulate' over a parent's life course, leading to larger differences in health by children's education as parents age (Ross and Wu 1996;Dannefer 2003). While a considerable amount of evidence suggests that age may be a leveller in high-income settings (Friedman and Mare 2014;Zimmer et al 2016;Elo et al 2018;Wolfe et al 2018;Sabater et al 2019;Yahirun et al 2020), relatively little is known about the age gradient in low-resource settings. Similarly, the benefits of children's education may also vary by geographical region.…”
Section: Effect Heterogeneitymentioning
confidence: 99%
“…Evidence on the health benefits of children's education for older generations dates back to at least the early 2000s (Zimmer et al 2002). Since then, a consistent positive association has been identified between children's education and a wide range of parental health outcomes, including: (1) parental mortality (Torssander 2013;Friedman and Mare 2014;Elo et al 2018;Smith-Greenaway et al 2018;Wolfe et al 2018;Sabater et al 2019); (2) parental physical health (Yahirun et al 2016(Yahirun et al , 2017Meyer et al 2019); and (3) parental mental health (Sabater and Graham 2016;Lee 2018;Peng et al 2019;Yahirun et al 2020). These associations persist after controlling for parents' demographic and socio-economic characteristics (De Neve and Kawachi 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the educational level of older adults contributes to better health, especially among the “younger old” (Sabater et al 2020 ; Leopold 2018 ; Torssander 2013 ). The Swedish system should be built on the assessment of the need for care.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the relationship between education and health [ 6 , 29 ]. At the same time, several economics studies have suggested that children’s education has a positive spillover effect on parents’ health [ 20 , 30 ]. This effect exists not only in China, but also in the United States [ 10 ], South Africa [ 11 ], and Europe [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in rural areas, the relationship between parents and adult children’s support is characterized by reciprocity. There is a significant positive correlation between parents’ investment in their children’s education and the old-age return provided by adult children [ 20 ]. Investment in children’s education in the early stage of children’s lives can improve the quality of life of parents once they pass the age of 65.…”
Section: Theoretical Analysismentioning
confidence: 99%